2010
DOI: 10.1111/j.1464-410x.2009.08894.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeat dynamic sentinel node biopsy in locally recurrent penile carcinoma

Abstract: of these patients had previously had a unilateral inguinal node dissection for groin metastases. The median disease-free interval was 18 months. The protocol and technique of primary dynamic SNB and the repeat procedure were similar, including preoperative lymphoscintigraphy and bluedye injection. Completion inguinal node dissection was only done if there was an involved sentinel node.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…40 Repeat biopsy is advised when the FNA is negative and the clinical suspicion is high. 41 A prolonged trial of antibiotics is no longer considered appropriate. Individuals with histologically positive nodes should undergo therapeutic ipsilateral radical inguinal lymph node dissection, 42 with modified dissection on the contralateral side.…”
Section: Clinically Involved Lymph Nodesmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Repeat biopsy is advised when the FNA is negative and the clinical suspicion is high. 41 A prolonged trial of antibiotics is no longer considered appropriate. Individuals with histologically positive nodes should undergo therapeutic ipsilateral radical inguinal lymph node dissection, 42 with modified dissection on the contralateral side.…”
Section: Clinically Involved Lymph Nodesmentioning
confidence: 99%
“…Efforts to improve accuracy have led to the development of several nomograms. [41][42][43][44] Three important points should be noted: (1) these tools remained largely unvalidated in prospective studies; 41 (2) not all features can be determined for individuals undergoing penile conserving treatment; and (3) sensitivity, specificity, and false-negative rate are variable and are inferior to recent reports of high sensitivity (94%) using dynamic sentinel node biopsy. 45,46 Therefore when available, DSNB is preferred for risk stratification over nomograms.…”
Section: Clinically Uninvolved Lymph Nodesmentioning
confidence: 99%
“…We were interested to read the report on repeat sentinel lymph node biopsy (SLNB) by Graafland et al . [1]. Their study showed lymphatic dissemination was re‐established in the groins after previous SLNB.…”
mentioning
confidence: 99%
“…We thank doctors Zhu and Ye for their interest in our article [1]. They present a recurrent penile cancer case who appeared to have direct lymphatic drainage to the pelvic lymph nodes (LNs) after previous bilateral inguinal LN dissection.…”
mentioning
confidence: 99%
“…This case and our publication highlight several aspects in the management of recurrent penile cancer that we would like to bring to attention. First, every local penile tumour can be a new source of lymphatic regional spread [1,2]. Renewed nodal staging is therefore of importance.…”
mentioning
confidence: 99%